Analisa Lapisan Perkerasan (Overlay) Pada Ruas Jalan Karya Wiguna Kelurahan Tegalgondo Kabupaten Malang (STA 0+000 – 1 +000) - Epong , Kordianus (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Roughness of a road that has been serving the traffic, will experience changes in road surface roughness and structure entirely. For it to be given an extra layer to be returned has a value of strength, comfort level, security level, the level of kedapan to water and level speed water flows as planned. Factors affecting thick layers of traffic load is added, the performance of the old road roughness, temperature and type of add layer used. The Add method of the thick layers of planning used in the standards work of wiguna village tegalgondo malang is bina marga indonesia method is a modification of the method of AASHTO 1972 Revision 1981 modification aims to penyusain the environment, the basic soil properties and types of layers that are generally in use in indonesia, in this study the author will discuss the planning process calculation of additional roughness layer (overlay) on road works wiguna. The results of the analysis showed a thick layer to the bottom of the Foundation (sub base) 20 cm thick with an aggregate class B, the Foundation (Base course) 15 cm thick with an aggregate class B, the surface layer (surface) 5 cm laston and able to serve traffic for 10 years.